Pembelajaran Humanistik pada Pendidikan Agama bagi Anak Berkebutuhan Khusus di Sekolah Inklusi - Anifah, Siti (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2023)
The aim of this research is to find out how religious education is taught using a humanistic approach for children with special needs at Darut Taqwa Vocational School, to find out the parameters for the success of learning religious education for ABK with a humanistic approach and to find out the supporting and inhibiting factors for learning religious education for ABK with a humanistic approach. This type of research is descriptive qualitative using a phenomenological approach. The research results show that religious education learning through a humanistic approach for ABK is in the quite effective category. This can be seen from the special attention given by religious education teachers to students with special needs so that they can follow and understand the learning well. The success of religious education for children with special needs using a humanistic approach has been considered quite successful, this can be seen when in learning students feel happy and not differentiated from regular students, they can read iqro', understand hijaiyah letters, can do questions, students' progress after learning is better compared to before. Supporting factors for learning Islamic religious education with a humanistic approach include: the presence of special teachers from special schools, teaching staff who have undergone inclusion training, facilities and infrastructure that have been adapted to the needs of children with special needs, school support, and the existence of a humanistic approach. Inhibiting factors include children with special needs who have difficulty listening to explanations during learning, teachers who are not yet experts in using sign language, and there are no standard minimum criteria.